Toward Sustainable Desert Architecture: Recent Studies in the Negev, Israel - Pearlmutter, David (Annals of Arid Zone, 2016)
What is meant by the term desert architecture? Why should buildings or towns in arid regions be conceived differently than they are anywhere else, and what would make such an architecture sustainable? This article discusses a number of ways that architectural design may be adapted to the opportunities and constraints of a desert climate, and in so doing allow for dramatic increase in the efficiency of energy consumption - which is perhaps the greatest challenge for long-term sustainability. A series of recent examples, taken from both research and application in the arid Negev region of Israel, is presented to illustrate some of the concrete possibilities for creating more sustainable patterns of desert architecture.